Dois ensaios sobre as emissões de gases de efeito estufa do BRIC : uma análise de insumo-produto - Oliveira, Manuela Macedo (2019)
The growing concern about the environment raises questions about the effects of economic growth on environmental degradation. One of the most relevant contemporary environmental problems is global warming, whose main cause is the intensification of greenhouse gases (GHG) emissions in the atmosphere. Historically, developed countries are primarily responsible for global warming, but in recent decades developing countries, among them the BRIC countries (Brazil, Russia, India and China), have continuously increased their emissions. Therefore, the dissertation consists of two essays and aims to study the GHG emissions of the BRIC countries from the input-output matrices and GHG emissions from the World Input-Output Database (WIOD). In the first test, the structural decomposition analysis method is used to decompose the factors responsible for the evolution of the BRIC emissions from 1995 to 2009. The main results indicate that there was no significant change in the emission profile of the countries. In Brazil, agricultural exports was the factor that contributed most to the increase of emissions in the period. In Russia, the intermediate demand of the industrial sector, mainly electricity and gas and water supply, stood out. In India and China, the final demand for industrial sectors had the greatest participation in increasing both countries' emissions. It is observed that the increase of the emissions of the emerging countries has occurred concomitant to the stabilization in developed countries, fomenting the hypothesis of pollution escape from the relations of international trade. In this sense, the second essay aims at structurally analyzing international trade from the input-output method, and identifying the emissions embodied in the BRIC countries' exports and imports in 1995, 2000, 2005 and 2009. The main results indicate that the four BRIC countries were net exporters of GHG emissions in the analyzed period, with particular emphasis on Russia.